2021
DOI: 10.37425/eajsti.v2i2.224
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Electronic Health Record Data for Computational Phenotyping of Diabetes Mellitus at Nairobi Hospital, Nairobi City County, Kenya

Abstract: This research aims to determine the applicability of routine healthcare in clinical informatics research.  One of the key areas of research in precision medicine is computational phenotyping from longitudinal Electronic Health Record (EHR) data. The objective of this research was to determine how the interplay of EHR software design, the use of a data dictionary, the process of data collection, and the training and motivation of the human resource involved in the collection and entry of data into the EHR affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…All points that are within eps of a core point are termed density-reachable and are considered to be part of a cluster. The rest of the data points that are considered not density-reachable are all considered to be noise (Pekel and Özcan, 2018;Olwendo, Ochieng, and Rucha, 2021;Mehedi, Mollick, and Yasmin, 2022).…”
Section: Unsupervised Learning Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…All points that are within eps of a core point are termed density-reachable and are considered to be part of a cluster. The rest of the data points that are considered not density-reachable are all considered to be noise (Pekel and Özcan, 2018;Olwendo, Ochieng, and Rucha, 2021;Mehedi, Mollick, and Yasmin, 2022).…”
Section: Unsupervised Learning Modelsmentioning
confidence: 99%
“…As a matter of fact, Silhouette's analysis of the clusters of both the k-means and the fuzzy c-means reported that only about 30% had negative coefficients, meaning that a larger percentage of the dataset had been placed in the clusters they relatively belonged to. Therefore, a comparative analysis of the performances of machine learning methods needs to consider sampling from both the supervised and unsupervised algorithms and compare results within each of the two categories (Olwendo, Ochieng, and Rucha, 2020;Mehedi, Mollick, and Yasmin, 2022).…”
Section: Model Performance For the Fuzzy C-means Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor glycemic control among diabetes patients is associated with the occurrence of diabetes complications, estimated to be approximately 34.6% among adults in Kenya 8 . A retrospective analysis of hospital data collected between 2012 and 2016 showed retinopathy, neuropathy and cardiovascular diseases to be the most common diabetes complications among patients, with a prevalence of 12%, 11%, and 11%, respectively 9 , among which diabetes nephropathy is the leading cause of death 10 .…”
Section: Introductionmentioning
confidence: 99%